Untersuchung eines gewissen Operators im Raume der im Einheitskreise analytischen Funktionen - Kirjackis, E. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Э. Г. Кирьяцкий. Об одном операторе в пространстве аналитических в единичном круге функций E. Kirjackis. Vieno operatoriaus, apibrėžto analizinių vienetiniame skritulyje funkcijų erdvėje, tyrimas